Prevalence of skin diseases in female prisoners in Turkey: Analysis of impact of prison conditions and psychological stress - (:unkn) unknown (Croatian Dermatovenerological Society, 2014)
Prisons have been studied as communal places where risk of contagious diseases and dermatological diseases associated with stress are more frequent. We aimed to investigate the prevalence of skin diseases in female prisoners with special focus on psychological stress. We held a day-time dermatology polyclinic for 6-weeks. The patients were given Beck Depression Inventory (BDI) and a questionnaire on the psychological impact of skin disease. A total of 383 female prisoners were examined; 41 dermatological diseases were diagnosed. Acne was the most prevalent condition (34%), followed by hair loss (19%), dry skin (16%), and eczema (12%). Thirty-six percent of the prisoners felt embarrassed, 34% felt anxious, and 45% felt sad about their skin disease. Fourty seven of the responders were found to be in severe depression according to BDI responses. We could not fnd any association between BDI results and any kind of skin disease diagnosed in inmates. Our study demonstrates that prisoners have benign and common skin conditions similar to those in the general population.
Keywords: Depression; Female prisoners; Prisoners; Quality of life; Skin diseases